Reinterpretation of the RRISP-77 Iceland shear-wave profiles - Menke, William; Brandsdóttir, Bryndís; Einarsson, Páll; Bjarnason, Ingi Th. (Geophysical Journal International, 1996)
Two shear-wave profiles, E and G, collected during the 1977 Reykjanes Ridge Iceland Seismic Experiment have played an important role in models of the Icelandic crust. They were originally interpreted as indicating very low shear-wave velocities and abnormally low shear-wave quality factors in the 10–15 km depth range. These attributes, which are indicative of near-solidus temperatures, were used to support the hypothesis that the crust of Iceland is relatively thin (10–15 km) and underlain by partially molten material. More recent seismic data, however, contradict this hypothesis and suggest that the crust is thicker (20–30 km) and cooler. A re-examination of the RRISP-77 data indicates that the low shear-wave velocities are artefacts arising from source static anomalies (in the case of profile G) and misidentification of a secondary shear phase, S m S , as S (in the case of profile E). Furthermore, the attenuation occurs at ranges when rays from the shots pass near the Askja (profile E) and Katla and Oraefajokull (profile G) volcanoes. It may therefore have a localized source, and not be diagnostic of Icelandic crust as a whole. This new interpretation of the RRISP-77 shear-wave data is consistent with models having a thick, cold crust.